Clinical features of pure obsessive-compulsive disorder - Torres, Albina Rodrigues [UNESP]; Shavitt, Roseli G.; Torresan, Ricardo C. [UNESP]; Ferrão, Ygor A.; Miguel, Euripedes C.; Fontenelle, Leonardo F. (Elsevier, 2013)
Objective Psychiatric comorbidity is the rule in obsessive-compulsive disorder (OCD); however, very few studies have evaluated the clinical characteristics of patients with no co-occurring disorders (non-comorbid or pure OCD). The aim of this study was to estimate the prevalence of pure cases in a large multicenter sample of OCD patients and compare the sociodemographic and clinical characteristics of individuals with and without any lifetime axis I comorbidity. Method A cross-sectional study with 955 adult patients of the Brazilian Research Consortium on Obsessive-Compulsive Spectrum Disorders (C-TOC). Assessment instruments included the Yale-Brown Obsessive-Compulsive Scale, the Dimensional Yale-Brown Obsessive-Compulsive Scale, The USP-Sensory Phenomena Scale and the Brown Assessment of Beliefs Scale. Comorbidities were evaluated using the Structured Clinical Interview for DSM-IV Axis I Disorders. Bivariate analyses were followed by logistic regression. Results Only 74 patients (7.7%) presented pure OCD. Compared with those presenting at least one lifetime comorbidity (881, 92.3%), non-comorbid patients were more likely to be female and to be working, reported less traumatic experiences and presented lower scores in the Y-BOCS obsession subscale and in total DY-BOCS scores. All symptom dimensions except contamination-cleaning and hoarding were less severe in non-comorbid patients. They also presented less severe depression and anxiety, lower suicidality and less previous treatments. In the logistic regression, the following variables predicted pure OCD: sex, severity of depressive and anxious symptoms, previous suicidal thoughts and psychotherapy. Conclusions Pure OCD patients were the minority in this large sample and were characterized by female sex, less severe depressive and anxious symptoms, less suicidal thoughts and less use of psychotherapy as a treatment modality. The implications of these findings for clinical practice are discussed. © 2013 Elsevier Inc. All rights reserved.
Keywords: adult; aggression; agoraphobia; body dysmorphic disorder; clinical feature; comparative study; compulsion; cross-sectional study; disease course; female; generalized anxiety disorder; human; major clinical study; major depression; male; obsession; obsessive compulsive disorder; phobia; posttraumatic stress disorder; prevalence; psychologic assessment; social phobia; structured interview; treatment duration; Yale Brown Obsessive Compulsive Scale